Novel approach on the synthesis of starch betainate by transesterification - Sharma, Mohit (2021)
Transesterification of starch with methyl betainate was studied for the first time, both in aprotic media and in solid state, and both under alkaline and acidic conditions. Betaine hydrochloride was first esterified in methanol, attaining a conversion of 86%. Starch was then converted into starch betainate in either N,N-dimethylformamide or dimethyl sulfoxide, and using sulfuric acid as catalyst or pre-activating the polymer in NaOH/ethanol. Furthermore, solid-state transesterification was carried out in a ball mill, for which sulfuric acid was replaced with the less corrosive sulfamic acid. Cationic starch esters were characterised by 1H and 13C NMR spectroscopy, infrared spectroscopy, thermogravimetric analysis, viscometry, optical microscopy (in water) and scanning electron microscopy (dry). In solution, the process attained degrees of substitution up to 0.4. No by-products, dehydration, oxidation or colouring were detected, but starch underwent severe depolymerization in wet media. In solid state, whilst the resulting degree of substitution was lower, degradation was minimal. In any case, transesterification, with its variety of possibilities, yields cationic starches that offer a promising alternative to conventional ethers.